2020
DOI: 10.3390/cancers12030625
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Thyroglobulin and Its Correlation with the Burden and Extent of Differentiated Thyroid Cancer

Abstract: Lymph node metastasis (LNM) in differentiated thyroid cancer (DTC) is usually detected with preoperative ultrasonography; however, this has limited sensitivity for small metastases, and there is currently no predictive biomarker that can help to inform the extent of surgery required. We evaluated whether preoperative serum thyroglobulin levels can predict tumor burden and extent. We retrospectively reviewed the clinical records of 4029 DTC cases diagnosed and treated at a Samsung Medical Center between 1994 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
2
24
0
3
Order By: Relevance
“…On the other hand, the raised level of Tg was frequently used for predicting the recurrence of PTC patients with reasonable sensitivity and specificity during the postoperative follow-up. But some recent studies (28,29) have proved that serum Tg level was markedly related to distant lymph node metastasis and skip metastasis in PTC patients. However, we did not include this factor in the further analysis as a result of it could be impaired by the HT condition, especially in the presence of TgAb.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the raised level of Tg was frequently used for predicting the recurrence of PTC patients with reasonable sensitivity and specificity during the postoperative follow-up. But some recent studies (28,29) have proved that serum Tg level was markedly related to distant lymph node metastasis and skip metastasis in PTC patients. However, we did not include this factor in the further analysis as a result of it could be impaired by the HT condition, especially in the presence of TgAb.…”
Section: Discussionmentioning
confidence: 97%
“…The initial and follow-up evaluation entails the measurement of TSH, serum TG levels, and neck sonogram, before RAI for diagnostic or therapeutic purposes was recommended by the American Thyroid Association (ATA) guidelines [7,8]. The ATA task force guidelines for the evaluation of thyroid cancer have evolved and recommend that patients with WDTC should be classified accordingly into low-, intermediate-, and high-risk groups It should be stressed that a universal increase in the prevalence of WDTC in thyroidectomized patients requires monitoring of these patients for recurrent or permanent disease through periodic (6-12 months) serum thyroglobulin (TG) estimation and anatomic imaging [9,10]. Patient management is then guided on this stratification according to the recurrence of the disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…16 Although thyroglobulin does not distinguish thyroid cancer from normal thyroid tissue, some studies 17,18 have shown that preoperative detection of thyroglobulin may help predict the tumor burden and lymph node metastasis of patients. A study in South Korea 19 believes that patients with preoperative thyroid globulin above 13.15ng/mL can be considered to have ipsilateral cervical lymph node metastasis, while above 30.05ng/mL may also have contralateral cervical lymph node metastasis, if higher than 62.9 ng/mL is at risk for distant metastases. Therefore, although thyroglobulin cannot be used as a marker for the diagnosis of thyroid cancer, it has a pivotal position in the management of thyroid cancer.…”
Section: Markers Related To Thyroid Functionmentioning
confidence: 99%